Traditional Games and Sports of the Women in the Kabylie - Nefil, Iman; Laaouad-dodoo, Soraya; Bordes, Pascal; Torki, Ahmed (Frontiers in Psychology, 2021)
Traditional games are an important part of the world's recreational cultural heritage. However, they remain little valued, even neglected to the detriment of other games, and especially sports in addition to the invasion and playful technology which more overwhelmingly predominates in children's pastimes in general. This study focuses on traditional sports games in Kabylie. Games circumscribed in a problematic of the otherness of the sexes, taken and defined as an object of study in the field of motor praxeology, a discipline initiated by the work of Pierre Parlebas. This led us, through a field survey, to try to identify and interpret the meaning and the distribution of the traditional games of Kabylie. From this perspective, the approach method based on the analysis of the internal logics of the practices analyzed, relates a system of interactions between the players and their environment. This reveals valuable information on the structures underlying traditional games, and their ethno-motor characteristics, as well as the world of ethnology in this vast mountainous region of Kabylie. The analysis of 92 traditional games played in the region of Kabylie allowed us to highlight on the one hand the cultural specificity and on the other hand the richness of the socio-cultural aspects of this region. By questioning how play constitutes a cultural identity element of a geographical space which is that of Kabylie, we refer to the meaning of playful culture and identity, by focusing more particularly on the place of women and the indicators that will distinguish the distribution female and male roles. This will allow us to understand the nature of traditional play and differentiated socialization between boys and girls. Keywords: Traditional games - Algerian society - women - culture - motor praxeology - socialization - Kabylie.